Smart Assisted Vehicle for Disabled/Elderly using Raspberry Pi - Shubham Pandey; Shubham Chandewar; Krishnamoorthy A. (International Journal of Reconfigurable and Embedded Systems (IJRES), 2017)
Independent mobility is a key component in maintaining the physical and psychosocial health of an individual. Further, for people e having disabled/elderly, independent mobility increases vocational and educational opportunities, reduces dependence on caregivers and family members, and promotes feelings of self-reliance. Psychologically, a decrease in mobility can lead to feelings of emotional loss, anxiety, depression, educed self-esteem, social isolation, stress, and fear of abandonment. Even though the benefits of powered mobility are well documented, the safety issues associated with operation of powered vehicles often prevent clinicians and rehabilitation practitioners from prescribing powered mobility. So we are introducing an intelligent vehicle for disables/elderly people which uses an array of sensors to help with the movement of the vehicle with minimal human interaction. Functionalities of the proposed system are further enhanced using android interface connect to the vehicle via Bluetooth.